O IDEB e as implicações na qualidade do ensino e na dinâmica escolar em instituições da rede municipal de São Luís/MA - RIBEIRO, Maria Luiza Miranda (2022)
This dissertation investigated “IDEB and the implications for the quality of teaching and school dynamics in institutions of the Municipal Network of São Luís/MA”. It aims to analyze the ways in which IDEB's implications for the quality of teaching and school dynamics are manifested in the perception of school professionals and in official quantitative data. SAEB and IDEB in SIMAE, the way in which IDEB is used in schools and, consequently, in the specific education system, and the implications for the school and its professionals. This study was defined as analytical descriptive, which includes bibliographic research. Documentary analysis and empirical-analytical research on the perception of school professionals about IDEB and SIMAE. The locus of the research was chosen from the criteria of interest of the research, being selected two schools, being the instrument of data collection an online questionnaire sent to all the professionals of the school, however not all returned. The information was submitted to Content Analysis based on Bardin (2011). For theoretical- methodological foundation, texts by: Almerindo Afonso, Stephen Ball, Nigel Brooke, Dourado e Oliveira, Dias Sobrinho, Luís Carlos de Freitas, Dalila Oliveira and Bresser Pereira, Silva and others were used. The research indicates that one cannot understand the IDEB without relating it to the State reform movements in the development of capitalist production and the influence of neoliberal doctrine and its result from a regulatory policy through Large- Scale Assessment of Basic Education in Brazil. Brazil. Based on IDEB results, advances in interference in the school and in the work of its professionals can be seen, with greater control over autonomy, management, curriculum, planning and modeling of the teacher's pedagogical profile. However, this movement does not seem to be significant in raising educational quality, influenced by internal and external factors to the school.